Evaluation of the tear film in eyes with pterygium and after its surgical excision using the limbal inferior-lateral conjunctival autotransplantation procedure - Celeva Markovska, Vesna (My University, 2010)
Aim To determine the eventual abnormalities of the tear function at patients with unilateral pterygium and after its surgical excision using conjunctival autotransplantation from the limbal inferior-lateral conjunctiva. Method The tear function was examined on 60 patients with unilateral pterygium before and after surgical excision of the pterygium with conjunctival autotransplantation using the graft from the limbal inferior-lateral conjunctiva. Schirmer test with and without local anesthetic and the break-up time of the tear film were used on the healthy eye, the eye with pterygium and after the pterygium surgery on the same patient. Results The mean time of the tear film break-up time (BUT) is 13,4 sec (10,7 sec - 16,2 sec) on the healthy eye. This mean time was significantly shorter, 5,6 sec (9,7 sec ± 4,7 sec), in the same patients but measured at the eye with pterygium. After 1 month of the operation and excision of the pterygium the mean time of the BUT was significantly longer (11,7sec ± 2,7 sec). Measured by the Schirmer test, the size of the wet area on the Whatman filter paper with local anesthesia was 14mm (12mm - 16mm) on the healthy eye and 4,5mm (3,0mm - 6,0mm) on the eye with pterygium. Postoperatively, the size of the wet area increased, i.e. the area was 14,8mm (12,7mm – 16,9mm). The wet area’s size measured by the Schirmer test without local anesthesia before the surgery of pterygium was 4,80 mm (3,50 mm - 6,1mm), after the surgery 15,50mm (13,5mm -17,50mm) and on the healthy eye 16mm (15,0mm-17,0mm). Conclusion The tear function in patients with primary pterygium improves after its surgical excision with the conjunctival autotransplantation using the graft from the limbal inferior-lateral conjunctiva. Thus it can be concluded that pterygium has a close relationship with the dryness of the eye.
Keywords: pterygium; limbal autotransplantation procedures; dry eye